2006
DOI: 10.2141/jpsa.43.235
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Lactobacillus Sporogenes on Performance and Serum Biochemico-Lipid Profile of Broiler Chickens

Abstract: An experiment was conducted to study the e#ect of dietary supplementation of probiotic Lactobacillus sporogenes (L. sporogenes) on performance and serum biochemico-lipid profile of broiler chickens. One hundred and twenty, day-old commercial broiler chicks were distributed equally into -groups of .* chicks each, which was further replicated to 2 groups of / each. The chicks were placed on one of three dietary treatments : basal, basal with probiotic (0ῌ+* 2 spore of Lactobacillus sporogenes per g) at +** or ,*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
63
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 23 publications
21
63
6
1
Order By: Relevance
“…They also found HDL-cholesterol was marginally increased. 7 Panda et al 8 also reported this probiotic is able to reduce total cholesterol, VLDL and triglycerides in broiler chickens.…”
Section: Introductionmentioning
confidence: 95%
“…They also found HDL-cholesterol was marginally increased. 7 Panda et al 8 also reported this probiotic is able to reduce total cholesterol, VLDL and triglycerides in broiler chickens.…”
Section: Introductionmentioning
confidence: 95%
“…Some authors have investigated the effects of adding a single level of probiotics in broiler diet (Khosravi et al 2010, Mountzouris et al 2007, Zakeri and Kashefi 2011), while others have tested two (Anjum et al 2005, Mehr et al 2007, Nayebpor et al 2007, Panda et al 2006 or three or more levels of probiotic supplementation (Apata 2008, Li et al 2008, Mountzouris et al 2010, Wang and Gu 2010. However, the results obtained are contradictory and highlight the importance of evaluating probiotic administration level for maximizing effi cacy.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics have been defined as a live microbial feed supplement that can beneficially affect the intestinal microbial balance, resulting in improved body weight gain and reduce mortality in broiler chickens. Prebiotics are defined as nondigestible, but fermentable food ingredients that beneficially affect the host by selectively stimulating the growth and activity of one or a limited number of species of probiotics bacteria in the colon (Panda et al, 2006). Symbiosis is defined as a combination of a probiotics and a prebiotics, aimed to increase the survival activity of probiotics in vivo and stimulating indigenous bifido bacteria and Lactobacillus (Dughera et al, 2007).…”
Section: Introductionmentioning
confidence: 99%